Sistem Diagnosis Penyakit Hati Menggunakan Metode Naive Bayes - Novianto Donna Prayoga; Nurul Hidayat; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
System Diagnosis of Liver Disease using Naive Bayes Method is an application that aims to help people for diagnosing liver disease early. This system is built based on problems that occur in society that is difficult in liver disease. Because liver disease has many symptoms and there are similarities in symptoms. This is one of the causes of high percentage of liver disease in Indonesia, recorded from Basic Health Research in 2013, one type of liver disease that is national hepatitis B prevalence reached 21.8 percent, and ranked third highest in Indonesia.The Naive Bayes method was chosen in this study because Naive Bayes paid attention to all features of data training so as to make this method optimal in classification process. This system uses the Android operating system, because Android is quite consistent popularity in the market smarthphone Indonesia until now. The data used in this study were obtained from doctor who have been validated by the institution of Universitas Brawijaya Hospital, Malang. The results of this study indicate base on the accuracy testing of 40 data testing obtained an accuracy of 87,5%.